Determining the Correlation Between Lateral Radiograph Morphology and the Outcome Following Surgically Treated Intra-Articular Calcaneal Fractures. Issue 2 (April 2021) - Nooijen, Lynn E.; Spierings, Kimberley E.; Sanders, Fay R. K.; Dingemans, Siem A.; Halm, Jens A.; Schepers, Tim
Purpose . It is currently still common practice to obtain conventional radiographs in the follow-up of surgically treated displaced intra-articular calcaneal fractures at regular intervals. There is, however, insufficient evidence that these radiographs can be used to predict functional outcome. The aim of the current study was to evaluate the correlation between the most commonly used angles on lateral radiographs and disease-specific patient-reported outcome measures (PROMs). Methods . Two available databases, containing a total of 233 patients, were used in this study. Eleven angles on the lateral images of the preoperative and at 1-year follow-up radiographs were measured. The 6 most commonly used angles were also measured immediately postoperatively. These 6 most commonly used angles were correlated with PROMs (American Orthopaedic Foot and Ankle Society hindfoot score, Foot Function Index) by a Spearman's rho analysis. After a Bonferroni correction was applied, a P value of <.0042 was considered to be statistically significant. Results . After exclusion of bilateral fractures, primary arthrodesis, open fractures, wound infections, other wound complications, nonavailable radiographs, and nonresponders, 86 patients remained. No significant correlations were found between the measured angles on the preoperative and at 1-year follow-up radiographs and the PROMs. Conclusion . No apparent correlation between lateral radiograph morphology and outcome was detected. Therefore, long-term follow-up radiographs after confirmed healing may be restricted to patients with persistent complaints on indication. Levels of Evidence: Prognostic, Level IV: Retrospective